2017
DOI: 10.1590/1980-5373-mr-2017-0300
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Optimization for Heat Treatment of Al-Si-Mg Alloy Prepared by Indirect Squeeze Casting Based on Response Surface Methodology

Abstract: The purpose of the present study is to model and analyze heat treatment process of Al-Si-Mg alloy prepared by indirect squeeze casting. The combined effects of whole heat treatment process, including solution treatment temperature, solution treatment time, ageing temperature and ageing time, on Vickers hardness, were investigated. The non-linear mathematical model has been developed through BoxBehnken design based on response surface methodology. The results of ANOVA tests have proven the model is capable of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…From a scientific and technological aspect, no intrinsic novelty was obtained, as previous investigations [10,16,23,33,35] have also reported similar UTS values. It is recognized that Mg2Si particles decrease mechanical behavior [21][22][23]38]. Additionally, it has been found that its dissolution occurs at solutioning, and this process is commonly rapidly obtained, i.e., between 2 and 4 min [38].…”
Section: Quenching and Aging Effects On Mechanical Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…From a scientific and technological aspect, no intrinsic novelty was obtained, as previous investigations [10,16,23,33,35] have also reported similar UTS values. It is recognized that Mg2Si particles decrease mechanical behavior [21][22][23]38]. Additionally, it has been found that its dissolution occurs at solutioning, and this process is commonly rapidly obtained, i.e., between 2 and 4 min [38].…”
Section: Quenching and Aging Effects On Mechanical Behaviormentioning
confidence: 99%
“…In the field of material science and engineering, extensive literature addresses Al-Sibased and A356 alloys, scrutinizing various manufacturing conditions, Si morphology modifiers, and different heat treatments [4,8]. The literature reported [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][29][30][31][32][33][34][35][36][37][38] has shown a great gamma of studies. When the PRISMA concept (preferred reporting items for systematic reviews and meta-analyses), stringers "Al-Si-based alloys", and "eutectic" are utilized when searching articles, more than 1400 papers are obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The black-patterned eutectic Al-Mg 2 Si phase and a black bulk-like primary Mg 2 Si phase can be observed in all samples. The dissolution and homogenization of Mg 2 Si particles are a rapid process [20]. Al-Mg 2 Si can be considered as a simple pseudobinary alloy, which is particularly useful for simplifying the thermodynamics of an Al-Mg-Si system at a specific ratio in a binary phase diagram [5,21].…”
Section: Calphad Calculationmentioning
confidence: 99%
“…[3] The squeeze casting technology can be divided into direct squeeze casting and indirect squeeze casting. [4] Indirect squeeze casting uses the forming punch to squeeze the liquid metal into the mold cavity and pass the pressure to the casting through the inner runner composed of a punch and a concave mold. Compared with the die casting process, this squeeze casting process can effectively improve the casting shrinkage and forming ability, avoid and reduce the casting defects such as porosity, and improve the mechanical properties of casting.…”
Section: Introductionmentioning
confidence: 99%